2024
DOI: 10.1007/s00436-024-08141-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the European badger a new host for Dirofilaria immitis? The first records in Greece

Grigorios Markakis,
Georgios Sioutas,
Dimitra Bitchava
et al.

Abstract: Dirofilaria immitis is a ubiquitous nematode parasite with zoonotic potential, transmitted by mosquitoes, that causes heartworm disease in various animal species. Dogs are the parasite’s typical final host, and wild carnivores represent the parasite’s reservoir in nature. Studies on D. immitis infections in wild animals are essential to assess infection pressure for domestic animals, and until now, there has been only one infection case reported in a European badger (Meles meles). The current report describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The role of wild animals in the epizootiology of dirofilariosis should not be underestimated. It has been proven that D. immitis infects many wild mammalian species, such as golden jackals ( Canis aureus ), wolves ( Canis lupus ), coyotes ( Canis latrans ), red foxes ( Vulpes vulpes ), European wildcats ( Felis silvestris silvestris ), black bears ( Ursus americanus ), brown bears ( Ursus arctos ) and European badgers ( Meles meles ) [ 47 , 48 ]. In addition, cardiopulmonary dirofilariosis has been identified as one of the leading causes of death in wildlife animals [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of wild animals in the epizootiology of dirofilariosis should not be underestimated. It has been proven that D. immitis infects many wild mammalian species, such as golden jackals ( Canis aureus ), wolves ( Canis lupus ), coyotes ( Canis latrans ), red foxes ( Vulpes vulpes ), European wildcats ( Felis silvestris silvestris ), black bears ( Ursus americanus ), brown bears ( Ursus arctos ) and European badgers ( Meles meles ) [ 47 , 48 ]. In addition, cardiopulmonary dirofilariosis has been identified as one of the leading causes of death in wildlife animals [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, there is a lack of data regarding the exact epizootiological role of wildlife animals in transmitting D. immitis since their role as definitive hosts for this parasite has not been adequately investigated [ 47 ]. In Greece, there are limited studies, and the presence of the parasite has been documented in a golden jackal [ 50 ], a brown bear [ 51 ], and most recently in two European badgers [ 48 ]. In the latter study, the presence of microfilariae in both badgers was detected, thus corroborating this wildlife species as a competent host.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlighted the role of this species as an additional reservoir host for D. immitis . In more detail, this study suggested that dirofilariosis occurs in the indigenous wildlife of Crete Island, an area which, based on the available data, currently, is not regarded as endemic for dirofilariosis ( Markakis et al, 2024 ). Interestingly, a recent ecological niche modeling analysis study for Culex pipiens , the main vector of D. immitis in Greece, revealed that the environment in Crete is suitable for the mosquito to complete its life-cycle and the future infection risk in that area is high ( Rodríguez-Escolar et al, 2024 ).…”
Section: Omnivoresmentioning
confidence: 91%
“… 94 6.4 b Touloudi et al (2015) Cestoda Echninococcus granulosus 273 1.1 Chaligiannis et al (2015) European badger ( Meles meles ) Protozoa Eimeria spp. 2 50.0 Liatis et al (2017) Nematoda Dirofilaria immitis 2 100 Markakis et al (2024) Brown rat ( Rattus norvegicus ) Protozoa Leishmania infantum 16 6.2 c Papadogiannakis et al (2010) 19 70.0 b , 0 d Tsakmakidis et al (2017) Black rat ( Rattus rattus ) Protozoa Leishmania infantum 12 50.0 b , 25.0 d Tsakmakidis et al (2017) House mouse ( Mus musculus ) Protozoa Leishmania infantum 66 50.0 b , 24.0 d Tsakmakidis et al (2017) European hedgehog ( Erinaceus europaeus ) …”
Section: Omnivoresmentioning
confidence: 99%
See 1 more Smart Citation